Vanek's tumor as an uncommon cause of digestive bleeding - Morínigo, Sergio (2025)
Gastrointestinal tract polyps exhibit a wide range of characteristics, from benign to potentially malignant lesions. Vanek's polyp, a rare entity, is characterized by its inflammatory infiltrate and vascular alterations, often leading to confusion with adenomatous lesions. We present the case of a 77-year-old woman with a one-month history of rectal bleeding, requiring hospitalization during one of the episodes. Colonoscopy revealed a pedunculated polyp, which was resected without complications. Histopathological analysis showed a lymphoplasmacytic infiltrate, multiple vessels with fibrinoid necrosis, and no neoplastic atypia. Due to the nonspecific nature of the report, immunohistochemical studies were performed, revealing CD34 positivity in the vessels and vimentin positivity in mesenchymal cells. These findings suggest a differential diagnosis from inflammatory fibroid polyps. Vanek’s polyps are uncommon lesions that require accurate diagnosis and appropriate management. Recent trends show an increase in the identification of these polyps, likely due to advancements in diagnostic techniques.